How Does Usable Security (Not) End Up in Software Products? Results From a Qualitative Interview Study - Gutfleisch, Marco; Klemmer, Jan H.; Busch, Niklas; Acar, Yasemin; Sasse, M. Angela; Fahl, Sascha (43rd IEEE Symposium on Security and Privacy, SP 2022, San Francisco, CA, USA, May 22-26, 2022)

27 Years and 81 Million Opportunities Later: Investigating the Use of Email Encryption for an Entire University - Stransky, Christian; Wiese, Oliver; Roth, Volker; Acar, Yasemin; Fahl, Sascha (43rd IEEE Symposium on Security and Privacy, SP 2022, San Francisco, CA, USA, May 22-26, 2022)

Where to Recruit for Security Development Studies: Comparing Six Software Developer Samples - Kaur, Harjot; Amft, Sabrina; Votipka, Daniel; Acar, Yasemin; Fahl, Sascha (31st USENIX Security Symposium, USENIX Security 2022, Boston, MA, USA, August 10-12, 2022)

They Would Do Better If They Worked Together: Interaction Problems Between Password Managers and the Web - Huaman, Nicolas; Amft, Sabrina; Oltrogge, Marten; Acar, Yasemin; Fahl, Sascha (IEEE Secur. Priv.)

"Please help share!": Security and Privacy Advice on Twitter during the 2022 Russian Invasion of Ukraine - Schmüser, Juliane; Wöhler, Noah; Ramulu, Harshini Sri; Stransky, Christian; Wermke, Dominik; Fahl, Sascha; Acar, Yasemin (CoRR)

Technically enabled explaining of voice characteristics - Wiechmann, Jana; Glarner, Thomas; Rautenberg, Frederik; Wagner, Petra; Haeb-Umbach, Reinhold (18. Phonetik und Phonologie im deutschsprachigen Raum (P&P))

Erkenntnisse aus Arbeitgeberbewertungen – Potenzial von Atmosphäre und Arbeitsplätzen. - Radermacher, Katharina; Herdejürgen, Enja Marie (PERSONALquarterly)

Long‐term effects of institutional conditions on perceived corruption – A study on organizational imprinting in post‐communist countries - Auer, Thorsten Fabian; Knorr, Karin; Thommes, Kirsten (Business Ethics, the Environment & Responsibility)
In this paper, we apply imprinting theory to examine how institutional transformation substantially influences perceptions of corruption that we argue to be incorporated to a varying extent in organizations founded in that period. For this purpose, we compare the effect of a sudden shock (dissolution of the Soviet Union) on the managers' present perceptions to that of a steady transition (EU accession). We consult the 5th round of the Business Environment and Enterprise Performance Survey from 2012 to 2014 analyzing 4715 interviews with managers of organizations from twelve Central and Eastern European countries. Our results reveal striking differences in the present perception of corruption for organizations founded immediately before and immediately after these institutional transitions. The study's results contribute to the research on imprinting theory regarding the relationship between organizations and institutional conditions that constitutes a lasting effect on organizational structures. Thus, applying an institutional perspective that considers less stable periods for organizations yields a promising avenue in research on organizational behavior.
Keywords: Central and Eastern Europe; corruption; imprinting theory; institutional transformation; shock-imprinting

Die Wirksamkeit von Lernzielen für Studienleistungen – eine experimentelle Studie - Auer, Thorsten Fabian (die hochschullehre)
According to the German Rectors’ Conference (HRK), German higher education teaching fails to meet the demand to integrate competence-oriented learning objectives. Despite a wide-ranging debate on the use of learning objectives, empirical research on their effectiveness is scarce. The present study uses the features of digital teaching platforms to investigate the perception and effectiveness of learning objectives applying a randomised controlled experiment followed by a survey in a course for undergraduate economics students (N = 30). Controlling group preconditions and the treatment effect allows to draw conclusions about the different learning outcomes of the student groups. The specification of behaviour-oriented learning objectives in the online course system leads to significantly better performance in the treatment group. A stronger perception of the learning objectives in the treatment group supports this effect that remains significant in a regression analysis. Thus, the study provides an empirical justification to integrate learning objectives in university teaching.
Keywords: learning objectives; academic performance; perception; teaching methods; experiment

AI-Based Assistance System for Manufacturing - Deppe, Sahar; Brandt, Lukas; Brünninghaus, Marc; Papenkordt, Jörg; Heindorf, Stefan; Tschirner-Vinke, Gudrun
Manufacturing companies are challenged to make the increasingly complex work processes equally manageable for all employees to prevent an impending loss of competence. In this contribution, an intelligent assistance system is proposed enabling employees to help themselves in the workplace and provide them with competence-related support. This results in increasing the short- and long-term efficiency of problem solving in companies.
Keywords: Assistance system; Knowledge graph; Information retrieval; Neural networks; AR

AI-Based Assistance System for Manufacturing - Deppe, Sahar; Brandt, Lukas; Brunninghaus, Marc; Papenkordt, Jörg; Heindorf, Stefan; Tschirner-Vinke, Gudrun (2022 IEEE 27th International Conference on Emerging Technologies and Factory Automation (ETFA))

Determinants of Trust in Smart Technologies - Papenkordt, Jörg; Thommes, Kirsten (Human-Technology Interaction)

Warum werde ich nicht satt? Begehren und Begehrt-Werden bei den Ärzt*innen der Utopie. Grey’s Anatomy aus einer inklusiven religionspädagogischen Perspektive - Neumann, Anna (Lust und Abgrund. Theologische und kulturwissenschaftliche Zugänge zum Begehren)

Die Frage der Apostasie im Islam – Rationale Behandlung von Adlabī und El-ʿAwwā - Abdelrahem, Mohammed (Rationalität in der Islamischen Theologie Band II: Die Moderne)
Keywords: islamisches Recht. islamische Normenlehre; islamic law; Apostasie; Rationalität; Islam

Rationalität in der Islamischen Theologie II: Die Moderne

Ich habe nur die eine Hälfte genommen – Verstehensprozesse zur Achsensymmetrie - Wallner, Melina (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Erkenntnisse aus Arbeitgeberbewertungen: Das Potential von Arbeitsatmosphäre und Arbeitsplatzgestaltung für die Weiterempfehlungsbereitschaft (Studie Industrieverband Büro und Arbeitswelt e. V. (IBA).)

Verification of safety critical control policies using kernel methods - Vertovec, Nikolaus; Ober-Blöbaum, Sina; Margellos, Kostas
Hamilton-Jacobi reachability methods for safety-critical control have been well studied, but the safety guarantees derived rely on the accuracy of the numerical computation. Thus, it is crucial to understand and account for any inaccuracies that occur due to uncertainty in the underlying dynamics and environment as well as the induced numerical errors. To this end, we propose a framework for modeling the error of the value function inherent in Hamilton-Jacobi reachability using a Gaussian process. The derived safety controller can be used in conjuncture with arbitrary controllers to provide a safe hybrid control law. The marginal likelihood of the Gaussian process then provides a confidence metric used to determine switches between a least restrictive controller and a safety controller. We test both the prediction as well as the correction capabilities of the presented method in a classical pursuit-evasion example.

Gottesbilder in den Deuteropaulinen. Metaphernrezeption im Kontext von Bildfeldtraditionen - Taschl-Erber, Andrea (Gottes-Bilder. Zur Metaphorik biblischer Gottesrede (Beiträge zur Wissenschaft vom Alten und Neuen Testament 232))

"Von dem, der getragen wurde durch die Vier und Rettung erfuhr. Ein etwas anderer Blick in die Erzählung von der Heilung des Gelähmten in Mk 2,1-12" - Breuer, Saskia Rebecca (Der Dom. Katholisches Magazin im Erzbistum Paderborn)